How university students changed their habits and developed mental disorders in the context of the coronavirus disease 2019 (COVID‐19) pandemic in Japan: Three case reports. Issue 3 (20th July 2022) - Nagaoka, Maiko; Kubo, Hiroe; Tashiro, Kuniko; Kinoshita, Maiko; Inoue, Hiroko; Soejima, Hirofumi; Fujise, Noboru
Abstract: Background: Since the COVID‐19 pandemic reached Japan in 2020, the country has faced an unprecedented increase in suicide rate and school refusal among adolescents, as well as increased rates of depression and anxiety among young people. However, the effects of the COVID‐19 pandemic on adolescents in terms of changes in habits, the development of mental disorders, social isolation, and suicidal ideation remain largely unclear. Case Presentation: We examined three cases of university students who changed their habits during the COVID‐19 pandemic and developed mental disorders. All three cases had similar habitual changes, experienced loneliness, and developed depression and circadian rhythm sleep–wake disorder. Their habitual changes were delayed sleep and wake times, delayed first mealtime, a tendency to eat before sleeping, decreased social contact, increased digital media usage, and a tendency to use digital media before going to bed. We established a model of increasing mental health difficulties, school refusal, and suicidal ideation during the COVID‐19 pandemic. Conclusion: This report suggests possible approaches for preventing a decline in mental health during the COVID‐19 pandemic among university students. Abstract : We propose a model for how the COVID‐19 pandemic has changed university students' habits and exacerbated mental health difficulties. We describe three cases who exhibited changes in sleep time, eating time, time spent using digital media, social isolation, depressive mood, and suicidal ideation.